Are changes in patient-reported outcomes prognostic for diffuse large B-Cell lymphoma survival? Results from the GOYA trial - Jessie T. Yan; Célia Bel; Peter C. Trask; Ernest Lo (SpringerOpen, 2024)
Abstract In this hypothesis-generating analysis, we examined whether longitudinal changes in patient-reported outcomes (PROs), such as symptoms, over time would be prognostic for progression-free survival (PFS) and overall survival (OS) in patients with diffuse large B-cell lymphoma (DLBCL) who were newly treated with obinutuzumab (G) in combination with CHOP (G-CHOP) or rituximab (R) with CHOP (R-CHOP), in the GOYA Phase 3 trial (NCT01287741). Our results show that from the study baseline to cycle 3 day 1, every 1-point increase (worsening) in fever symptoms was associated with a 41% higher risk of death (hazard ratio [HR], 1.41; P = 0.01). Every 1-point increase (worsening) in lumps or swelling symptoms was associated with a 27% higher risk of disease progression or death (PFS events) (HR, 1.27; P = 0.01) and a 29% higher risk of death (OS events) (HR, 1.29; P = 0.02). No significant associations were observed between survival and changes in other symptoms, such as itching. Our study suggests that changes in some PROs are related to survival in DLBCL patients.